Kontraksi Manufaktur di Indonesia: Pengaruh Rasio Fundamental Terhadap Harga Saham pada Awal Pandemi Covid-19 - Nurwulandari (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to obtain empirical evidence about the effect of a company's fundamental ratio on stock prices. The financial ratios used in this study are Return on Assets (ROA), Return on Equity (ROE), Earnings per Share (EPS), Price Book Ratio (PBR) and Price Earnings Ratio (PER). This study uses secondary data obtained from the OSIRIS database. The sampling technique was taken using a purposive sampling method of 122 manufacturing companies registered on the IDX in 2020. The analysis used in this study was using the multiple linear regression analysis method, which was preceded by the classic assumption test - normality test, multicollinearity test and heteroscedasticity test. The results showed that ROA, EPS and PBR partially have a significant effect on stock prices with a positive relationship. Meanwhile, ROE and PER partially have a significant effect on stock prices with a negative relationship. Simultaneously, ROA, ROE, EPS, PBR and PER have a significant effect on stock prices. The results of this study indicate that some financial ratios are still very useful for predicting the value of a company's shares, therefore investors must pay attention to the existence of the company's fundamental financial ratios in influencing the investment decisions to be made.